EXPLORING THE ROLE OF WIRELESS SENSOR NETWORKS IN ENVIRONMENTAL MONITORING AND DISASTER MANAGEMENT - Ariffien , Afferdhy (KRIEZ ACADEMY : Journal of development and community service, 2024)
Background:Subscription-based marketing models have gained significant traction as a means of fostering long-term customer relationships. Businesses across industries, from streaming platforms to e-commerce and software services, are increasingly adopting these models to enhance consumer loyalty and retention. However, their effectiveness and key influencing factors require deeper exploration. Aims:This study examines the impact of subscription-based marketing models on consumer loyalty and retention, highlighting the critical determinants that drive long-term engagement and satisfaction among subscribers. Research Method:The research employs a mixed-method approach, combining qualitative interviews with quantitative survey data collected from 500 respondents across various industries using subscription services. Statistical analysis and thematic categorization are used to draw meaningful insights. Results and Conclusion:The findings indicate that personalization, perceived value, and consistent service quality are significant factors influencing consumer loyalty. Furthermore, flexible subscription options and proactive customer support enhance retention rates. The study concludes that businesses adopting these strategies are better positioned to maintain a competitive edge and sustain growth in the subscription economy. Contribution:This research contributes to marketing literature by providing a comprehensive analysis of subscription-based models and their role in consumer retention. It offers actionable insights for businesses seeking to optimize their strategies and enhance customer relationships.